2018
DOI: 10.1097/md.0000000000013553
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry identification of potential biomarker proteins in the 150-kD electrophoretic band in patients with schizophrenia

Abstract: Background:Diagnosing schizophrenia is primarily based on the presentation of defined signs and symptoms, none of which is pathognomonic for this group of syndromes. However, few significant genome-wide associations between schizophrenia and individual have detected. Protein profiling of candidate serum biomarkers in schizophrenia is therefore an area of great interest.Methods:In the present study, we used a combination of 7% polyethylene glycol (PEG) enrichment of immune complexes and sodium dodecyl sulfate-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Evidence reported that the collagen chain gene (COL1A1) expression might be associated with the EMC ligands, thus resulting in the inactivation of DDR1 with a timedependent decrease in the SZ patients 58 . In addition, evidence reported that COL1A1 and COL1A2 genes expression levels were signi cantly decreased in patients with SZ compared to control 59 . One of the most increased genes, COL3A1, is detected, which encodes the pro-1 chains of type III collagen and exhibits a de novo mutation in SZ patients 60 .…”
Section: Identi Ed Targets Validation With Literature Reviewmentioning
confidence: 99%
“…Evidence reported that the collagen chain gene (COL1A1) expression might be associated with the EMC ligands, thus resulting in the inactivation of DDR1 with a timedependent decrease in the SZ patients 58 . In addition, evidence reported that COL1A1 and COL1A2 genes expression levels were signi cantly decreased in patients with SZ compared to control 59 . One of the most increased genes, COL3A1, is detected, which encodes the pro-1 chains of type III collagen and exhibits a de novo mutation in SZ patients 60 .…”
Section: Identi Ed Targets Validation With Literature Reviewmentioning
confidence: 99%
“…In other postmortem studies, a reduced brain expression of LAMA1, FN1, COL4A1, and COL4A2 has been previously reported in schizophrenia [12]. In a serum proteomic analysis of paranoid schizophrenia patients, researchers found reductions in COL4A1 but not COL4A2, although this effect was not significant [106]. De novo mutations have been identified in schizophrenia for LAMA1 (missense mutation) [87] and LAMA2 (frameshift and splice site mutations) [107].…”
Section: Brain Microvascular Abnormalities In Schizophreniamentioning
confidence: 99%
“…These proteins have been proposed as biomarker candidates for prognosis, diagnosis, and medication monitoring in SCZ (72,73). One of these proteins is zinc finger protein 729 that was found significantly downregulated in patients with SCZ compared to healthy individuals and patients diagnosed with depression or BD (74). Another example is the study that showed reduced plasma levels of glia maturation factor beta (GMF-b), the brain-derived neurotrophic factor (BDNF), and the 115-kDa isoform of the Rab3 GTPaseactivating protein catalytic subunit (RAB3GAP1) in SCZ patients.…”
Section: Proteomic Biomarkers In Neuropsychiatrymentioning
confidence: 99%